2008
DOI: 10.1021/pr700671z
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transfer Dissociation of Peptides Generated by Microwave D-Cleavage Digestion of Proteins

Abstract: The nonenzymatic digestion of proteins by microwave D-cleavage is an effective technique for site-specific cleavage at aspartic acid (D). This specific cleavage C-terminal to D residues leads to inherently large peptides (15-25 amino acids) that are usually relatively highly charged (above +3) when ionized by electrospray ionization (ESI) due to the presence of several basic amino acids within their sequences. It is well-documented that highly charged peptide ions generated by ESI are well-suited for electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…By using LC-ESI-LTQ-Orbitrap and acetic acid digestion, Swatkoski et al showed that database search with CID MS/MS (for small peptide) was successful with some modification on the MAS-COT enzyme rules [6]. For larger and highly charged Aspcleavage peptides, ETD (and ECD) was found by Hauser et al to be more suitable than CID to yield larger sequence coverage [37].…”
Section: Resultsmentioning
confidence: 99%
“…By using LC-ESI-LTQ-Orbitrap and acetic acid digestion, Swatkoski et al showed that database search with CID MS/MS (for small peptide) was successful with some modification on the MAS-COT enzyme rules [6]. For larger and highly charged Aspcleavage peptides, ETD (and ECD) was found by Hauser et al to be more suitable than CID to yield larger sequence coverage [37].…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Hauser et al microwave digestion occurs very fast (,6 min) and subsequent ETD analysis results in sufficient fragment ions for confident peptide identification. The performance and rapidness of the method are ideal for an ETD application in high-throughput proteomics [43].…”
Section: Other Proteasesmentioning
confidence: 99%
“…As a result, these CID mass spectra are not as informative in terms of amino acid sequence because the localization of charges on basic groups along the backbone of the peptide does not allow for sufficiently random fragmentation. In fact, the high charge state peptides produced by the microwave D-cleavage method have been shown to be better suited for Electron Transfer Dissociation (ETD) than for CID, the former technique favoring ions with charge states higher than +2, and thus providing a high percentage of sequence coverage32. Conversely, direct comparison of CID tandem mass spectra of peptides generated by microwave D-cleavege and trypsin digestion showed improved peptide sequence coverage for the tryptic peptide over the microwave-generated peptide32.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the high charge state peptides produced by the microwave D-cleavage method have been shown to be better suited for Electron Transfer Dissociation (ETD) than for CID, the former technique favoring ions with charge states higher than +2, and thus providing a high percentage of sequence coverage32. Conversely, direct comparison of CID tandem mass spectra of peptides generated by microwave D-cleavege and trypsin digestion showed improved peptide sequence coverage for the tryptic peptide over the microwave-generated peptide32. This behavior is expected to be similar for the echem WY-cleavage derived peptides since tryptophan and tyrosine have a combined frequency in protein sequences of 3.99 %31.…”
Section: Introductionmentioning
confidence: 99%